Catalytic enantioselective 5-endo-bromocycloetherification of unactivated cyclic alkenes. (6th July 2022) - Xiong, Haoran; Yoshida, Kei; Okada, Kosuke; Ueda, Hirofumi; Tokuyama, Hidetoshi
Graphical abstract: Abstract: This study reports the development and scope of catalytic enantioselective 5- endo -trig bromocycloetherification of six-membered unactivated alkenes having a hydroxyethyl group. The proposed reaction occurs in a chiral anionic phase-transfer catalytic system using a combination of a binaphthol-based chiral phosphoric acid and a derivative of DABCO bromine complex to provide bicyclic tetrahydrofuran-fused 6-membered products, which bear a bromo group at the bridgehead position with complete diastereoselectivity and good to high enantioselectivity. Results show that the enantioselectivity depends on the solvent system and substituents at the 3, 3′-position of the catalyst. Thus, the best result can be obtained using a catalyst that has 2, 4, 6-tricyclohexylphenyl groups at the 3, 3′-positions in a mixture of fluorobenzene and n -heptane. In addition, the construction of a quaternary carbon center with the retention of configuration via a radical mediated allylation of the tertiary bromo group in the product was reported.